2022
DOI: 10.1177/03913988211073344
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) for cardiogenic shock during out of hours versus working hours is not associated with increased mortality

Abstract: Background: Initiation of veno-arterial (VA) Extracorporeal Membrane Oxygenator (ECMO) is associated with severe complications. It is unknown whether these adverse consequences occur more often after initiations during out of hours service compared to working hours. Methods: All patients receiving VA-ECMO for cardiogenic shock between 2009 and 2020 were categorized into a working hours group (between 8 am and 5 pm on weekdays) and an out of hours service group (between 5 pm and 8 am, or between Friday 5 pm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Studies on large-bore veno-arterial extracorporeal membrane oxygenation (VA-ECMO) have produced conflicting results regarding higher rates of vascular complications during off-hours implantation. 12,13 The VA-ECMO technique, even when implanted on-hours had significantly higher rates of vascular ischemia and bleeding compared to the present pVAD study making it difficult to compare the two. Regarding pVAD implantation, the current study found higher complication rates off-hours.…”
Section: Reasons Of Higher Left Ventricular Assist Device-complicatio...mentioning
confidence: 56%
“…Studies on large-bore veno-arterial extracorporeal membrane oxygenation (VA-ECMO) have produced conflicting results regarding higher rates of vascular complications during off-hours implantation. 12,13 The VA-ECMO technique, even when implanted on-hours had significantly higher rates of vascular ischemia and bleeding compared to the present pVAD study making it difficult to compare the two. Regarding pVAD implantation, the current study found higher complication rates off-hours.…”
Section: Reasons Of Higher Left Ventricular Assist Device-complicatio...mentioning
confidence: 56%